Analisis Filosofis Masa Depan Pendidikan di Perguruan Tinggi Indonesia-Malaysia dalam Menghadapi Tantagan Era Megatrend 2045 - Aliyah R. B; Nurmahmudah, Fitri; Pattiasina, Petrus Jacob; Darimis, Darimis; Malintang, Jimmy (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to conduct a philosophical analysis of the future of education in Indonesian-Malaysian universities in facing the challenges of the 2045 Megatrend era. The main focus of this research is to explore philosophical concepts that can guide the transformation of higher education in both countries to be relevant and adaptive to global developments, technology, and anticipated social demands by 2045. A literature approach is used in this study, by analyzing the literature on educational philosophy, social theory, and future developments related to higher education. Through philosophical analysis, it was found that higher education in Indonesia-Malaysia needs to adapt to the major changes faced in the 2045 Megatrend era. Concepts such as value-based education, continuous learning, technological adaptation, and social inclusion are key in preparing graduates who are ready to face the challenges of the future. In addition, cross-disciplinary and international collaboration, strengthening the capacity of lecturers, and integrating local values in the curriculum are also important factors to ensure the relevance and quality of higher education in the future